Analisis Perwilayahan dan Strategi Pengembangan Kunyit dan Jahe di Kabupaten Bondowoso - Adawiyah, Robiatul; Soetriono, Soetriono; Aji, Joni Murti Mulyo (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Biopharmaceuticals play an important role in maintaining health. One of the areas in East Java as a producer of biopharmaceuticals is Bondowoso Regency. Several sub-districts in Bondowoso Regency are able to produce several types of biopharmaceutical plants and the types most produced in Bondowoso Regency are ginger and turmeric. The large amount of biopharmaceutical production in Bondowoso Regency certainly has several problems, including prices at the farmer level are relatively fluctuating, the obstacles faced by some farmers are that contracts with companies are relatively difficult, production is relatively fluctuating with uneven distribution because it has not been able to be cultivated intensively. This research was conducted in Bondowoso Regency using the LQ, Localization, Specialization, Regional Multiplier, SWOT and QSPM methods. The results of this study are that Bondowoso Regency is a biopharmaceutical base sector, ginger and turmeric commodities are spread across several areas in Bondowoso Regency and do not specialize in one area in Bondowoso Regency, biopharmaceuticals have a multiplier effect on the agricultural subsector. Some of the strategies used are maintaining and improving the quality of ginger and turmeric in order to maintain cooperation with buyers, increasing awareness of the importance of consuming herbal products, getting support from government agencies, utilizing land for the cultivation process.